2018
DOI: 10.1371/journal.ppat.1007230
|View full text |Cite
|
Sign up to set email alerts
|

Killing with proficiency: Integrated post-translational regulation of an offensive Type VI secretion system

Abstract: The Type VI secretion system (T6SS) is widely used by bacterial pathogens as an effective weapon against bacterial competitors and is also deployed against host eukaryotic cells in some cases. It is a contractile nanomachine which delivers toxic effector proteins directly into target cells by dynamic cycles of assembly and firing. Bacterial cells adopt distinct post-translational regulatory strategies for deployment of the T6SS. ‘Defensive’ T6SSs assemble and fire in response to incoming attacks from aggressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 44 publications
2
37
0
Order By: Relevance
“…T6SS clusters from group 3 contain tagF-pppA-ppkA-fha genes, suggesting that activation of T6SS assembly and firing is dependent on the activation of the kinase PpkA, as originally described in P. aeruginosa (Mougous et al, 2007; Casabona et al, 2013). Recent work has demonstrated that PpkA acts by counteracting the inhibitory effect of TagF on T6SS activity, and the distinction between defensive and offensive T6SSs is mainly determined by the upstream input from protein(s) responsible for activation of PpkA (Lin et al, 2018; Ostrowski et al, 2018). In the defensive T6SS of P. aeruginosa , an incoming attack is sensed in the periplasm by TagQRST, while in the offensive Serratia marcensens T6SS, the signal is sensed by RtkS (Ostrowski et al, 2018).…”
Section: Regulation Of T6sssmentioning
confidence: 99%
See 1 more Smart Citation
“…T6SS clusters from group 3 contain tagF-pppA-ppkA-fha genes, suggesting that activation of T6SS assembly and firing is dependent on the activation of the kinase PpkA, as originally described in P. aeruginosa (Mougous et al, 2007; Casabona et al, 2013). Recent work has demonstrated that PpkA acts by counteracting the inhibitory effect of TagF on T6SS activity, and the distinction between defensive and offensive T6SSs is mainly determined by the upstream input from protein(s) responsible for activation of PpkA (Lin et al, 2018; Ostrowski et al, 2018). In the defensive T6SS of P. aeruginosa , an incoming attack is sensed in the periplasm by TagQRST, while in the offensive Serratia marcensens T6SS, the signal is sensed by RtkS (Ostrowski et al, 2018).…”
Section: Regulation Of T6sssmentioning
confidence: 99%
“…Recent work has demonstrated that PpkA acts by counteracting the inhibitory effect of TagF on T6SS activity, and the distinction between defensive and offensive T6SSs is mainly determined by the upstream input from protein(s) responsible for activation of PpkA (Lin et al, 2018; Ostrowski et al, 2018). In the defensive T6SS of P. aeruginosa , an incoming attack is sensed in the periplasm by TagQRST, while in the offensive Serratia marcensens T6SS, the signal is sensed by RtkS (Ostrowski et al, 2018). The offensive/defensive model has been described in only a few antibacterial T6SS and the mechanism of post-translational activation of anti-eukaryotic machines is possibly different.…”
Section: Regulation Of T6sssmentioning
confidence: 99%
“…During this process, involved in the defense of bacteria to a neighboring attack, a membrane-bound threonine kinase phosphorylates a forkheadassociated domain-containing Protein (FhA or TagH), which promotes the assembly of an active conformation of the T6SS at the site of the attack (52)(53)(54). Recently, the offensive antibacterial T6SS of Serratia marcescens has also been shown be controlled by the opposing actions of the TPP pathway and TagF on assembly of the core machinery (55). The TPP represents the only currently identified post-translational mechanism regulating T6SS biogenesis.…”
Section: Iglb Phosphorylation a New Mediator Of T6ss Dissociation?mentioning
confidence: 99%
“…There is remarkable variation in the regulation and use of T6SS weaponry across species. Bacteria activate and deploy the T6SS across a range of environmental contexts [16][17][18][19] and against both prokaryotic and eukaryotic targets [20][21][22] . The specific pattern of firing by cells also varies: whereas placement of T6SS assembly appears to be random in some species, such as Vibrio cholerae, Serratia marcescens, and Acinetobacter baylyi [23][24][25] , other bacteria are known to fire from specific locations on their cell membranes.…”
mentioning
confidence: 99%